EKSISTENSI TARI JEPIN TAMMBONG ENAM DI DESA KARIMUNTING KECAMATAN SUNGAI RAYA KEPULAUAN KABUPATEN BENGKAYANG - Dalamus, Renny Basajo; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to describe the existence of Tari Jepin Tammbong Enam in Karimunting village. The problem of this research is related to the existence of Tari Jepin Tammbong Enam and the factors that affect the development of Tari Jepin Tammbong Enam. This study uses descriptive method with a qualitative form and ethnographic approach.Â The data source of this study is approach colleted from the interview, the observation draft and the documentation of interviews with Suratmi, Matâ€™ani and Ruslan. The validity of data in tested by using triangulation techniques of the sources which compiled and analyzed systematically. The result of this study indicates: (1) Tari Jepin Tammbong Enam is still preserved by Sanggar Rukun Bersama since 1995. (2) The support systems of the existence of Tari Tammbong Enam are Sanggar Rukun Bersama, society, and government. (3) The obstacle factors of the existence of Tari Jepin Tammbong Enam is not interested to learn and nowadays young people assume that this kind of dance is outdated. (4) To built the awareness of young generation to involve in regional traditions especially Tari Jepin Tammbong Enam.Keywords: Existence, Tari Jepin Tammbong Enam